A Brief Review on Hydrogen production to Utilization Techniques - Qureshi, F. (Institute of Electrical and Electronics Engineers Inc., 2021)
Hydrogen is a clean source of energy and is being considered as the future of energy. Hydrogen is a promising alternative to fossil fuels since it has high calorific value and zero carbon emission after consumption. The vision of hydrogen economy may be the game changer in the energy sector and is encouraged via environmentalists as per the commitments made during the Paris Agreement. It is a green alternative that may help in reducing the human's dependence on fossil fuels and in regulating the global temperatures. The three main areas that need a rigorous attention are the hydrogen production, storage, and utilization techniques. This short review highlights the current trends and obstacles in the commercialization of hydrogen production, storage, and utilization techniques. Â© 2021 IEEE.